Challenges and solutions in medically managed ACS in the Asia-Pacific region: Expert recommendations from the Asia-Pacific ACS Medical Management Working Group. (15th March 2015) - Huo, Yong; Thompson, Peter; Buddhari, Wacin; Ge, Junbo; Harding, Scott; Ramanathan, Letchuman; Reyes, Eugenio; Santoso, Anwar; Tam, Li-Wah; Vijayaraghavan, Govindan; Yeh, Hung-I
Abstract: Acute coronary syndromes (ACS) remain a leading cause of mortality and morbidity in the Asia-Pacific (APAC) region. International guidelines advocate invasive procedures in all but low-risk ACS patients; however, a high proportion of ACS patients in the APAC region receive solely medical management due to a combination of unique geographical, socioeconomic, and population-specific barriers. The APAC ACS Medical Management Working Group recently convened to discuss the ACS medical management landscape in the APAC region. Local and international ACS guidelines and the global and APAC clinical evidence-base for medical management of ACS were reviewed. Challenges in the provision of optimal care for these patients were identified and broadly categorized into issues related to (1) accessibility/systems of care, (2) risk stratification, (3) education, (4) optimization of pharmacotherapy, and (5) cost/affordability. While ACS guidelines clearly represent a valuable standard of care, the group concluded that these challenges can be best met by establishing cardiac networks and individual hospital models/clinical pathways taking into account local risk factors (including socioeconomic status), affordability and availability of pharmacotherapies/invasive facilities, and the nature of local healthcare systems. Potential solutions central to the optimization of ACS medical management in the APAC region are outlined with specific recommendations.